Technological paradigms and the power of convergence. (7th August 2021) - Pedota, Mattia; Grilli, Luca; Piscitello, Lucia
Abstract: With the advent of Industry 4.0, technological interdependence is becoming increasingly important in the delineation of technological development dynamics. In the present paper, we propose an extension of the theory of technological paradigms conceptualizing the role of technological interdependence in the emergence of paradigms and the coevolution of the corresponding trajectories. We corroborate our conceptual extension by means of an in-depth historical account of the genesis and evolution of the additive manufacturing paradigm. Accordingly, we elucidate how different technological paradigms may give rise to an aggregate paradigm through a process of convergence and how the aggregate paradigm may contribute to steering the direction of technological change alongside traditional science-push, demand-pull, institutional, and socioeconomic factors. Our work has two main implications: first, it shows that a technological paradigm may emerge from a process of incremental convergence and not only from radical innovations and scientific breakthroughs. Second, it shows that the dynamics of epistemological interdependence (i.e., interdependence between paradigms) matter significantly in the determination of technological development paths.